PENGARUH PRINSIP-PRINSIP GOOD GOVERNMENT GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGAN YANG DI MODERASI OLEH KOMPETENSI SUMBER DAYA MANUSIA - Muksin Hadi; Hadady, Hartaty; Suwito (FEB Universitas Sam Ratulangi Manado, 2025)
Abstract: This study aims to determine and test the Influence of Good Government Governance Principles on the Quality of Financial Reports Moderated by Human Resource Competence. This study uses a quantitative approach, where the data used is in the form of numbers or quantitative data that has been processed. The population that is the focus of this study is the regional apparatus that is directly involved in the management of regional finances with, The sample in this study was represented by 4 parts, each OPD was taken by 4 respondents consisting of the Head of Didas/Agency, Secretary, Treasurer, Head of Program Sub-Division/Head of Finance Sub-Division. The data collection method was carried out through survey techniques and using questionnaires. The analysis method for testing the hypothesis in this study is Smart Partial Least Squares (SmartPLS 4.0). The test results show The test results show the influence between Accountability has a significant effect on the Quality of Financial Reports, Budget Transparency has a significant effect on the Quality of Financial Reports, Budget Participation does not have a significant effect on the Quality of Financial Reports, The test results show the influence between Human Resource Competence has a significant effect on the Quality of Financial Reports. The test results show that the influence of human resource competency is unable to moderate Accountability towards the Quality of Financial Reports and Human Resource Competence moderates Budget Participation which has a significant influence on the Quality of Financial Reports.